Comparison of Internet and face-to-face delivery of a group body image and disordered eating intervention for women: a pilot study. - Gollings E; Paxton S (Eating Disorders, 2006)
Increased access to therapy for body dissatisfaction and disordered eating is required. This pilot study compared a group intervention delivered face-to-face or synchronously over the Internet. Women with body dissatisfaction and disordered eating were randomly assigned to a face-to-face ( N = 19) or Internet ( N = 21) group. Body dissatisfaction, disordered eating, and psychological variables were assessed at baseline, post-intervention, and two months follow-up. Significant improvements on all outcome variables were observed and maintained at follow-up in both groups. There were no significant differences between delivery modes. This program shows promise, and the Internet mode of delivery has potential to overcome geographical distance.